Exploring ILP and heuristic formulations for planning multiband optical networks - Vaz, Margarida Isabel Carreto (2022)
To keep up with the growth in traffic demands in nowadays optical telecommunications networks, solutions such as multiband and flexible grid are needed to improve spectrum efficiency and transmission capacity. This dissertation focuses on planning the routing and wavelength assignment (RWA) in multiband networks using both heuristic and integer linear programming (ILP) solutions to optimize the spectrum allocation. We develop C+L multiband network planning tools to solve the RWA problem in static networks, using flexible and fixed grids, exploring different routing metrics, such as distance and optical signal-to-noise ratio. First, we compare the performance of two RWA tools, a heuristic and an ILP, considering a fixed grid, in terms of the number of wavelengths and computation time, for different network topologies. Then, we extend our RWA heuristic tool to deal with the flexible grid and be aware of the physical layer impairments, to be capable of solving routing, modulation format and spectrum assignment (RMSA) problems. We have concluded that our RWA ILP achieves the optimum number of wavelengths, when it uses more than one candidate path per demand but requires more computing time than the RWA heuristic tool. In RMSA problems, the number of allocated frequency slots (FSs) is dependent on the bit error rate (BER). Networks with shorter links require more FSs as the BER decreases. Networks with longer links require less FSs as the BER decreases, since the blocked demands increase.